Przemiany w podmiejskich i śródmiejskich społecznościach lokalnych w procesie gentryfikacji - Barczykowska, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2021)
The article presents socio-demographic, physical-functional and cultural-symbolic change aspects of chosen local communities in Poland, which aretheresult of the gentrification process, making itself real in their space. In the first part of the article information about genesis and the course of gentrification with the characteristic of the main actors’ groups taking part in it is addressed. The second part of the article is devoted to the description of changes being experienced by local communities. Conclusions included in the end concentrate around consequences of progressive gentrification process for local communities and attempts to set a path to prevent negative aspect of theconsequences mentioned.